Avaliação da capacidade máxima de hospedagem de minigeração e microgeração distribuída em alimentadores de média tensão - Medeiros, Natasha de Oliveira (2017)
Distributed Generation has caused important changes in its operating paradigm in the Electrical System and the development of tools that help from the concessionaire to the autoproducer in the control of flows and service to the system is extremely important. At present, defining the best connection points of the GD with the Distribution Network and how much power can be generated in these points without damaging the operation of the electric network is fundamental for the electric sector. This work addresses the determination of the maximum capacity of mini and microvolt generation in distribution networks, limited by the capacity of feeder sections, voltage limits and active losses. The resulting optimization problem is solved by using a Genetic Algorithm coupled to a power flow calculation module. The method was tested with a hypothetical system of 34 buses and a real distribution system of 134 buses. The results obtained in the tests indicate that the proposed approach produces adequate results, with computation time compatible with the intended application.